(untitled) (Journal of Medicine, 2009)
Background: Anti-Tuberculosis (TB) drug resistance is emerging as a new global health problem. No national data on drug resistance is available in Bangladesh. The absolute number of multidrug resistant TB (MDR-TB) is expected to be high considering high TB burden. This study was aimed to determine the resistance pattern of mycobacterium tuberculosis (MTB) isolates among different category of patient. Method: A total 1123 randomly selected patients having clinical and or radiological features of tuberculosis attending out patients department of NIDCH were enrolled in this study during January to December, 2008. Sputum were collected and processed for culture by digestion, decontamination and concentration following modified Petroff’s method and were inoculated on to two slopes of Lowenstein- Jensen (L-J) media for six weeks. The identity of the isolates was made by growth rate, colony morphology, P-nitrobenzoic acid (PNB) susceptibility, catalase and nitrate reduction tests. Ultimately drug susceptibility testing (DST) were performed. Result: Drug susceptibility testing for Isoniazid (INH), Rifampicin (RIF), Ethambutol (EMB) and Streptomycin (SM) was done among 363 cases. Resistance rates for INH, RIF, EMB and SM were 76.03%, 71.63%, 27.55% and 55.65% respectively. According to DST report, total 221 cases were detected as multi drug resistant TB (MDR-TB). Among them, 87% cases were MDR-TB in category II (CAT - II) failure and 13% were MDR-TB in category I (CAT - I) failure and it was 0% in new cases. Conclusion: Pattern of anti TB drug resistance was identified in this study. More surveillance and immediate therapeutic interventions should be performed in order to combat the threat of MDR-TB to the general population. Keywords: Tuberculosis, Multi drug resistance, Drug susceptibility testing. doi: 10.3329/jom.v10i2.2812 J MEDICINE 2009; 10 : 45-47